2013
DOI: 10.3151/jact.11.180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Water Molecules in Interlayer of 14 Å Tobermorite

Abstract: The molecular structure and dynamics of interlayer water of 14 Å tobermorite are investigated based on molecular dynamics (MD) simulations. Calculated structural parameters of the interlayer water configuration are in good agreement with current knowledge of the refined structure. The MD simulations provide detailed information on the position and mobility of the hydrogen and oxygen of interlayer water, as well as its self-diffusion coefficient, through the interlayer of 14 Å tobermorite. Comparison of the MD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Youssef et al [151] showed that the non-bridging oxygen atoms on the disordered silicate chains orient the hydrogen atoms of the interfacial water molecules toward the calcium-silicate layers, making the C-S-H nano-pore space hydrophilic. The orientation of water molecules in the interlayer of 14 Å tobermorite was obtained by molecular dynamics [152]. The characterization of water confined at ambient temperature inside a C-S-H grain (intragranular) and between C-S-H grains (intergranular) for different relative humidities at 300 K was done by Bonnaud et al [153].…”
Section: Atomistic Modelingmentioning
confidence: 99%
“…Youssef et al [151] showed that the non-bridging oxygen atoms on the disordered silicate chains orient the hydrogen atoms of the interfacial water molecules toward the calcium-silicate layers, making the C-S-H nano-pore space hydrophilic. The orientation of water molecules in the interlayer of 14 Å tobermorite was obtained by molecular dynamics [152]. The characterization of water confined at ambient temperature inside a C-S-H grain (intragranular) and between C-S-H grains (intergranular) for different relative humidities at 300 K was done by Bonnaud et al [153].…”
Section: Atomistic Modelingmentioning
confidence: 99%
“…But a distinction must be made between interlayer water, surface water and capillary or bulk water [76]. The auto-diffusion coefficient of interlayer water within the 9 to 14 Å layers of the crystalline structure of tobermorite, a C-S-H analogue, has been evaluated to 1.4 to 6.8×10 −11 m 2 /s from MD simulations [76][77][78][79] and 2.6 × 10 −11 m 2 /s from NMR experiments [80], which is about two orders of magnitude smaller than the value for bulk water equal to 2.3×10 −9 m 2 /s. The auto-diffusion coefficient of surface adsorbed water, located within less than 1nm to the C-S-H surface, has been estimated from 4.5 × 10 −10 to 1.2 × 10 −9 m 2 /s [76,79,80] i.e.…”
Section: Diffusion Properties Of the Different Phasesmentioning
confidence: 99%